Solid-state imaging element

The use of a cyanine dye with a crosslinked copolymer structure in solid-state image sensors addresses the issues of reduced transmittance and dye elution, enhancing heat resistance and stripping liquid resistance in infrared light cut filters.

JP2024175005AActive Publication Date: 2024-12-17TOPPAN HOLDINGS INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024158216
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17
Estimated Expiration
2040-07-03

AI Technical Summary

Technical Problem

Solid-state image sensors with infrared light cut filters face issues of reduced infrared light transmittance due to heating during soldering and elution of cyanine dye during dry etching, leading to compromised heat resistance and resistance to stripping liquids.

Method used

Incorporation of a cyanine dye with a copolymer containing polymethine, a cation with nitrogen-containing heterocycles, and tris(pentafluoroethyl)trifluorophosphate, along with a crosslinked structure formed by crosslinking a cyclic ether group of a first repeating unit with a functional group of a second repeating unit, which includes a phenolic hydroxyl group, to enhance heat resistance and resistance to stripping liquids.

Benefits of technology

The solution effectively maintains infrared light transmittance and prevents cyanine dye elution, thereby improving the heat resistance and stripping liquid resistance of the infrared light cut filter, ensuring consistent spectral characteristics and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024175005000001_ABST
    Figure 2024175005000001_ABST
Patent Text Reader

Abstract

To provide an infrared cut filter, a filter for a solid-state imaging element, a solid-state imaging element, and a method for manufacturing the filter for the solid-state imaging element in which heat resistance and resistance to a stripping liquid can be improved.SOLUTION: A solid-state imaging element 10 includes an infrared cut filter 13 and a photoelectric conversion element 11, the infrared cut filter 13 including polymethine, cations located one by one on both terminals of the polymethine and having two heterocyclic rings including nitrogen, a cyanine pigment including tris (pentafluoroethyl) trifluoro-phosphoric acid, and a copolymer. The copolymer is represented by the following formula (1) and includes a first repeating unit derived from an acryl monomer including a circular ester group and a second repeating unit derived from a monomer including a functional group which reacts with the circular ester group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid-state imaging device. [Background technology]

[0002] Solid-state imaging devices such as CMOS image sensors and CCD image sensors include photoelectric conversion elements that convert the intensity of light into an electrical signal. One example of a solid-state imaging device is capable of detecting light corresponding to a plurality of colors. The solid-state imaging device includes a color filter for each color and a photoelectric conversion element for each color, and detects light for each color by the photoelectric conversion element for each color (see, for example, Patent Document 1). Another example of a solid-state imaging device includes an organic photoelectric conversion element and an inorganic photoelectric conversion element, and detects light of each color by each photoelectric conversion element without using a color filter (see, for example, Patent Document 2).

[0003] The solid-state imaging element includes an infrared light cut filter on a photoelectric conversion element. The infrared light absorbing dye in the infrared light cut filter absorbs infrared light, thereby cutting off infrared light that can be detected by each photoelectric conversion element to the photoelectric conversion element. This improves the detection accuracy of visible light in each photoelectric conversion element. The infrared light cut filter contains, for example, a cyanine dye that is an infrared light absorbing dye (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2003-060176 A [Patent Document 2] JP 2018-060910 A [Patent Document 3] JP 2007-219114 A Summary of the Invention [Problem to be solved by the invention]

[0005] When a solid-state imaging element including an infrared cut filter is mounted on a mounting board, the solid-state imaging element is mounted on the mounting board by soldering using a reflow method. At this time, the infrared cut filter included in the solid-state imaging element is heated to a temperature at which the solder melts. Heating the infrared cut filter denatures the cyanine dye, and as a result, the infrared light transmittance of the infrared cut filter after heating may change from the infrared light transmittance of the infrared cut filter before heating.

[0006] On the other hand, dry etching may be used for patterning the infrared cut filter. In this case, a resist pattern is first formed on the infrared cut filter. Next, the infrared cut filter is etched using the resist pattern, and then the resist pattern is peeled off from the infrared cut filter. The stripping solution used to peel off the resist pattern from the infrared cut filter contacts the infrared cut filter, thereby dissolving a part of the cyanine dye contained in the infrared cut filter to the outside of the infrared cut filter. This reduces the amount of infrared light absorption expected in the infrared cut filter.

[0007] An object of the present invention is to provide a solid-state imaging device that is capable of improving heat resistance and resistance to a stripping solution. [Means for solving the problem]

[0008] A solid-state imaging element for solving the above-mentioned problems includes: a cyanine dye including polymethine, a cation having two nitrogen-containing heterocycles, one at each end of the polymethine, and tris(pentafluoroethyl)trifluorophosphate; an infrared light cut filter including a copolymer represented by the following formula (1) and including a first repeating unit derived from an acrylic monomer containing a cyclic ether group, and a second repeating unit derived from a monomer containing a functional group that reacts with the cyclic ether group; and a photoelectric conversion element.

[0009] [ka]

[0010] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is a single bond, a linear alkylene group having one or more carbon atoms, or a branched alkylene group having three or more carbon atoms, and R3 is a cyclic ether group containing an oxygen atom and two or more carbon atoms.

[0011] According to the above configuration, a crosslinked structure is formed by crosslinking a cyclic ether group of the first repeating unit with a functional group reactive with a cyclic ether group of the second repeating unit. This prevents the transmittance of the infrared cut filter from changing due to heating, and prevents the infrared absorbing dye from eluting into the stripping solution used during dry etching. As a result, it is possible to improve the heat resistance and resistance to the stripping solution of the infrared cut filter.

[0012] In the solid-state imaging device, the monomer containing a cyclic ether group may contain at least one of an epoxy group and an oxetanyl group. This configuration is preferable in terms of reactivity between the cyclic ether group and a functional group reactive with the cyclic ether group contained in the second repeating unit.

[0013] In the solid-state imaging device, the monomer including the functional group reactive with the cyclic ether group may be acidic. With this configuration, it is possible to prevent a crosslinking reaction from immediately proceeding at room temperature during the polymerization process of the resin.

[0014] In the solid-state imaging device, the functional group that reacts with the cyclic ether group may be a phenolic hydroxyl group. According to this configuration, since the phenolic hydroxyl group exhibits weak acidity, a crosslinking reaction with the cyclic ether group is unlikely to occur during the polymerization process of the resin, but is likely to occur during the heating step when forming the coating film. Therefore, the phenolic hydroxyl group is advantageous in terms of coatability.

[0015] In the solid-state imaging device, the copolymer may contain a third repeating unit derived from an acrylic monomer having an aromatic ring, represented by the following formula (2).

[0016] [ka]

[0017] In the formula (2), R4 is a hydrogen atom or a methyl group, and R5 is a single bond, a linear alkylene group having 1 or more carbon atoms, or a branched alkylene group having 3 or more carbon atoms. R6 is a hydrogen atom or a specific substituent. In the formula (2), when R6 is a substituent, m is an integer of 1 to 5.

[0018] In the solid-state imaging device, the copolymer may contain a third repeating unit derived from an acrylic monomer having an alicyclic structure represented by the following formula (3).

[0019] [ka]

[0020] In formula (3), R7 is a hydrogen atom or a methyl group, and R8 is a single bond, a linear alkylene group having 1 or more carbon atoms, or a branched alkylene group having 3 or more carbon atoms. In formula (3), R9 is an alicyclic structure having 3 or more carbon atoms.

[0021] According to the above-mentioned configuration, the aromatic ring group or alicyclic structure of the third repeating unit is located between the cyanine dye and another cyanine dye located in the vicinity of the cyanine dye, so that a distance sufficient to suppress association of the cyanine dyes can be formed between the cyanine dyes, thereby suppressing deterioration of the spectral characteristics at wavelengths expected to be absorbed by the cyanine dyes.

[0022] In the above solid-state imaging element, the copolymer may contain the first repeating unit in a proportion of 7.5% by weight or more and 17.5% by weight or less, and the ratio of the weight of the second repeating unit to the weight of the first repeating unit may be 1.0 or more and 3.0 or less.

[0023] According to the above configuration, since the copolymer contains the first repeating unit and the second repeating unit in the above range, the infrared light absorbance of the infrared cut filter is prevented from decreasing after the heat treatment and the stripping solution treatment, and this makes it possible to improve both the heat resistance and the resistance to the stripping solution of the infrared cut filter.

[0024] In the solid-state imaging device, the copolymer may contain the third repeating unit in a ratio of 65% by weight or more. According to this configuration, the copolymer containing the third repeating unit in the above range can suppress deterioration of the spectral characteristics at wavelengths expected to be absorbed by the cyanine dye in the infrared cut filter. The solid-state imaging device may further include a barrier layer that prevents the transmission of an oxidation source that oxidizes the infrared cut filter. The solid-state imaging device may include a visible light filter and an infrared light pass filter. In the solid-state imaging device, the oxygen permeability of the laminate structure located on the side of the incident surface with respect to the infrared light cut filter is 5.0 cc / m 2 It may be less than / day / atm. The solid-state imaging device may include a bandpass filter that transmits only light having a specific wavelength of visible light and near infrared light. Effect of the Invention

[0025] According to the present invention, it is possible to improve the heat resistance and resistance to a stripping solution in an infrared cut filter. [Brief description of the drawings]

[0026] [Figure 1]FIG. 1 is an exploded perspective view showing a structure of a solid-state imaging element according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] An embodiment of an infrared light cut filter, a filter for a solid-state imaging device, and a solid-state imaging device will be described with reference to Fig. 1. The solid-state imaging device, the manufacturing method for the filter for a solid-state imaging device, and examples will be described in order below. In this embodiment, infrared light is light having a wavelength in the range of 0.7 μm to 1 mm, and near-infrared light is infrared light having a wavelength in the range of 700 nm to 1100 nm.

[0028] [Solid-state imaging element] The solid-state imaging element will be described with reference to Fig. 1. Fig. 1 is a schematic diagram showing the individual layers of a portion of the solid-state imaging element in a separated manner.

[0029] 1, the solid-state imaging device 10 includes a solid-state imaging device filter 10F and a plurality of photoelectric conversion elements 11. The plurality of photoelectric conversion elements 11 include a red photoelectric conversion element 11R, a green photoelectric conversion element 11G, a blue photoelectric conversion element 11B, and an infrared light photoelectric conversion element 11P. The photoelectric conversion elements 11R, 11G, and 11B for each color measure the intensity of visible light having a specific wavelength associated with the photoelectric conversion element 11R, 11G, and 11B. Each infrared light photoelectric conversion element 11P measures the intensity of infrared light.

[0030] The solid-state imaging element 10 includes a plurality of red photoelectric conversion elements 11R, a plurality of green photoelectric conversion elements 11G, a plurality of blue photoelectric conversion elements 11B, and a plurality of infrared photoelectric conversion elements 11P. For convenience of illustration, Fig. 1 shows a repeating unit of the photoelectric conversion elements 11 in the solid-state imaging element 10.

[0031] The solid-state imaging device filter 10F includes a plurality of visible light filters, an infrared light pass filter 12P, an infrared light cut filter 13, a plurality of visible light microlenses, and an infrared light microlens 15P.

[0032] The visible light color filter is composed of a red filter 12R, a green filter 12G, and a blue filter 12B. The red filter 12R is located on the light incident side of the red photoelectric conversion element 11R. The green filter 12G is located on the light incident side of the green photoelectric conversion element 11G. The blue filter 12B is located on the light incident side of the blue photoelectric conversion element 11B.

[0033] The infrared light pass filter 12P is located on the light incident side of the infrared light photoelectric conversion element 11P. The infrared light pass filter 12P blocks visible light that can be detected by the infrared light photoelectric conversion element 11P from the infrared light photoelectric conversion element 11P. This improves the detection accuracy of infrared light by the infrared light photoelectric conversion element 11P. The infrared light that can be detected by the infrared light photoelectric conversion element 11P is, for example, near-infrared light.

[0034] The infrared cut filter 13 is located on the light incident side of the color filters 12R, 12G, and 12B. The infrared cut filter 13 has a through hole 13H. When viewed from a viewpoint opposite to the plane on which the infrared cut filter 13 extends, the infrared pass filter 12P is located within the area defined by the through hole 13H. On the other hand, when viewed from a viewpoint opposite to the plane on which the infrared cut filter 13 extends, the infrared cut filter 13 is located above the red filter 12R, the green filter 12G, and the blue filter 12B.

[0035] The infrared cut filter 13 contains a cyanine dye, which is an infrared light absorbing dye. The cyanine dye has a maximum value in the absorptivity of infrared light at any wavelength included in the near-infrared light. Therefore, the infrared cut filter 13 can reliably absorb the near-infrared light passing through the infrared cut filter 13. As a result, the near-infrared light that can be detected by the photoelectric conversion element 11 for each color is sufficiently cut by the infrared cut filter 13. The infrared cut filter 13 can have a thickness of, for example, 300 nm or more and 3 μm or less.

[0036] The barrier layer 14 suppresses the transmission of oxidizing sources of the infrared cut filter 13. The oxidizing sources are oxygen and water. The oxygen permeability of the barrier layer 14 is, for example, 5.0 cc / m 2 / day / atm or less. The oxygen permeability is a value in accordance with JIS K7126:2006. The oxygen permeability is 5.0cc / m 2 Since the infrared cut filter 13 is prevented from being reached by the barrier layer 14, the infrared cut filter 13 is less likely to be oxidized by the oxidation source. Therefore, the light resistance of the infrared cut filter 13 can be improved.

[0037] The material forming the barrier layer 14 is an inorganic compound. The material forming the barrier layer 14 is preferably a silicon compound. The material forming the barrier layer 14 may be, for example, at least one selected from the group consisting of silicon nitride, silicon oxide, and silicon oxynitride.

[0038] The microlenses are composed of a red microlens 15R, a green microlens 15G, a blue microlens 15B, and an infrared microlens 15P. The red microlens 15R is located on the light incident side of the red filter 12R. The green microlens 15G is located on the light incident side of the green filter 12G. The blue microlens 15B is located on the light incident side of the blue filter 12B. The infrared microlens 15P is located on the light incident side of the infrared light pass filter 12P.

[0039] Each of the microlenses 15R, 15G, 15B, and 15P has an incident surface 15S which is an outer surface. Each of the microlenses 15R, 15G, 15B, and 15P has a refractive index difference between itself and the outside air so as to collect light entering the incident surface 15S toward each of the photoelectric conversion elements 11R, 11G, 11B, and 11P. Each of the microlenses 15R, 15G, 15B, and 15P contains a transparent resin.

[0040] [Infrared cut filter] The infrared cut filter 13 will be described in more detail below. The infrared cut filter 13 includes a cyanine dye and a copolymer. The cyanine dye includes polymethine, a cation having two nitrogen-containing heterocycles, one at each end of the polymethine, and tris(pentafluoroethyl)trifluorophosphate (FAP) as an anion. The copolymer is represented by the following formula (1) and includes a first repeating unit derived from an acrylic monomer containing a cyclic ether group, and a second repeating unit derived from a monomer containing a functional group that reacts with a cyclic ether.

[0041] [ka]

[0042] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is a single bond, a linear alkylene group having one or more carbon atoms, or a branched alkylene group having three or more carbon atoms, and R3 is a cyclic ether group containing an oxygen atom and two or more carbon atoms.

[0043] The cyanine dye may have a structure shown in formula (4):

[0044] [ka]

[0045] In the above formula (4), X is a methine or polymethine. The hydrogen atom bonded to the carbon atom contained in the methine may be substituted with a halogen atom or an organic group. The polymethine may have a cyclic structure containing the carbons forming the polymethine. The cyclic structure may contain three consecutive carbons among the carbons forming the polymethine. When the polymethine has a cyclic structure, the number of carbons in the polymethine may be 5 or more. Each nitrogen atom is contained in a five-membered or six-membered heterocycle. The heterocycle may be condensed.

[0046] The cyanine dye may also have a structure shown in formula (5):

[0047] [ka]

[0048] In the above formula (5), n is an integer of 1 or more. n indicates the number of repeating units contained in the polymethine chain. R10 and R11 are hydrogen atoms or organic groups. R12 and R13 are hydrogen atoms or organic groups. R12 and R13 are preferably linear alkyl groups or branched alkyl groups having 1 or more carbon atoms. Each nitrogen atom is contained in a five-membered or six-membered heterocycle. The heterocycle may be condensed.

[0049] In the formula (4), when the polymethine contains a cyclic structure, the cyclic structure may be, for example, a cyclic structure having at least one unsaturated bond such as an ethylenic double bond, and the unsaturated bond may undergo electron resonance as a part of the polymethine chain. Such a cyclic structure may be, for example, a cyclopentene ring, a cyclopentadiene ring, a cyclohexene ring, a cyclohexadiene ring, a cycloheptene ring, a cyclooctene ring, a cyclooctadiene ring, or a benzene ring. Any of these cyclic structures may have a substituent.

[0050] In addition, in formula (5), a compound in which n is 1 is a cyanine, a compound in which n is 2 is a carbocyanine, and a compound in which n is 3 is a dicarbocyanine. In formula (5), a compound in which n is 4 is a tricarbocyanine.

[0051] The organic groups of R10 and R11 may be, for example, alkyl groups, aryl groups, aralkyl groups, and alkenyl groups. The alkyl groups may be, for example, methyl groups, ethyl groups, propyl groups, isopropyl groups, n-butyl groups, sec-butyl groups, isobutyl groups, tert-butyl groups, isopentyl groups, neopentyl groups, hexyl groups, cyclohexyl groups, octyl groups, nonyl groups, and decyl groups. The aryl groups may be, for example, phenyl groups, tolyl groups, xylyl groups, and naphthyl groups. The aralkyl groups may be, for example, benzyl groups, phenylethyl groups, and phenylpropyl groups. The alkenyl groups may be, for example, vinyl groups, allyl groups, propenyl groups, isopropenyl groups, butenyl groups, hexenyl groups, cyclohexenyl groups, and octenyl groups.

[0052] At least a part of the hydrogen atoms of each organic group may be substituted with a halogen atom or a cyano group. The halogen atom may be fluorine, bromine, chlorine, etc. The organic group after substitution may be, for example, a chloromethyl group, a chloropropyl group, a bromoethyl group, a trifluoropropyl group, a cyanoethyl group, etc.

[0053] R12 or R13 may be, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, a n-butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, an isopentyl group, a neopentyl group, a hexyl group, a cyclohexyl group, an octyl group, a nonyl group, and a decyl group.

[0054] Heterocycles containing each nitrogen atom may be, for example, pyrrole, imidazole, thiazole, pyridine, and the like. The cation contained in such a cyanine dye may have a structure represented by, for example, the following formula (6) or (7).

[0055] [ka]

[0056] [ka]

[0057] The cation contained in the cyanine dye may have, for example, a structure represented by the following formula (8) to formula (47). That is, each nitrogen atom contained in the cyanine dye may be contained in a cyclic structure represented by the following formula (8).

[0058] [ka]

[0059] [ka]

[0060] [ka]

[0061] [ka]

[0062]

change

[0063]

change

[0064]

change

[0065]

change

[0066]

change

[0067]

change

[0068]

change

[0069]

change

[0070]

change

[0071]

change

[0072]

change

[0073]

change

[0074]

change

[0075]

change

[0076]

change

[0077]

change

[0078]

change

[0079]

change

[0080]

change

[0081]

change

[0082]

change

[0083]

change

[0084]

change

[0085]

change

[0086]

change

[0087]

change

[0088]

change

[0089]

change

[0090]

change

[0091]

change

[0092]

change

[0093]

change

[0094] [ka]

[0095] [ka]

[0096] [ka]

[0097] [ka]

[0098] The cyanine dye has a maximum value of infrared light absorbance at any wavelength included in the range of 700 nm to 1100 nm. Therefore, the infrared light cut filter 13 can reliably absorb near-infrared light passing through the infrared light cut filter 13. As a result, the near-infrared light that can be detected by the photoelectric conversion element 11 for each color is sufficiently cut by the infrared light cut filter 13.

[0099] The absorbance Aλ at a wavelength λ is calculated by the following formula. Aλ=-log 10 (%T / 100) The transmittance T is represented by the ratio (TL / IL) of the intensity of transmitted light (TL) to the intensity of incident light (IL) when infrared light passes through an infrared cut filter 13 containing a cyanine dye. In the infrared cut filter 13, the intensity of transmitted light when the intensity of incident light is set to 1 is the transmittance T, and the value obtained by multiplying the transmittance T by 100 is the transmittance percentage %T.

[0100] Tris(pentafluoroethyl)trifluorophosphate ([(C2F5)3PF3] -) has a structure represented by the following formula (48):

[0101] [ka]

[0102] In the process of manufacturing the solid-state imaging device 10, the infrared cut filter 13 is heated to about 200° C. When the above-mentioned cyanine dye is heated to about 200° C., the structure of the cyanine dye changes, which may change the transmittance of the cyanine dye to infrared light.

[0103] In this respect, since the FAP has a molecular weight and a molecular structure that allows it to be located in the vicinity of the polymethine chain of the cyanine dye, the polymethine chain of the cyanine dye is prevented from being cut by heating the cyanine dye, and therefore, changes in the infrared light transmittance of the cyanine dye caused by heating the cyanine dye are prevented, and as a result, changes in the infrared light transmittance of the infrared cut filter 13 are prevented.

[0104] As described above, the infrared cut filter 13 includes a copolymer. The copolymer may include a repeating unit derived from a monomer containing acrylic acid or methacrylic acid. The monomer containing acrylic acid is an acrylate, and the monomer containing methacrylic acid is a methacrylate.

[0105] The copolymer includes a first repeating unit and a second repeating unit. The first repeating unit is derived from an acrylic monomer having a cyclic ether group. The second repeating unit is preferably derived from a monomer having a functional group that reacts with the cyclic ether group.

[0106] As described above, the first repeating unit is derived from an acrylic monomer having a cyclic ether group. In the first repeating unit, R1 is a hydrogen atom or a methyl group, and R2 is a single bond, a linear alkylene group having one or more carbon atoms, or a branched alkylene group having three or more carbon atoms. R2 may be, for example, a methylene group, an ethylene group, a trimethylene group, a propylene group, or a butylene group. R3 is a cyclic ether group containing an oxygen atom and two or more carbon atoms. The cyclic ether group has an ether bond in a ring formed by including a plurality of carbon atoms.

[0107] The cyclic ether group may be, for example, an epoxy group, an oxetanyl group, a tetrahydrofuranyl group, or a tetrahydropyranyl group. In terms of reactivity with the functional group of the second repeating unit, the cyclic ether group is preferably an epoxy group or an oxetanyl group. That is, the monomer containing a cyclic ether group preferably contains at least one of an epoxy group and an oxetanyl group.

[0108] Examples of the acrylic monomer having a cyclic ether group include glycidyl (meth)acrylate, 2-methylglycidyl (meth)acrylate, 2-ethylglycidyl (meth)acrylate, 2-oxiranylethyl (meth)acrylate, 2-glycidyloxyethyl (meth)acrylate, 3-glycidyloxypropyl (meth)acrylate, glycidyloxyphenyl (meth)acrylate, oxetanyl (meth)acrylate, 3-methyl-3-oxetanyl (meth)acrylate, 3-ethyl-3-oxetanyl (meth)acrylate, (3-methyl-3-oxetanyl)methyl (meth)acrylate, (3-ethyl-3 2-(3-methyl-3-oxetanyl)ethyl (meth)acrylate, 2-(3-ethyl-3-oxetanyl)ethyl (meth)acrylate, 2-[(3-methyl-3-oxetanyl)methyloxy]ethyl (meth)acrylate, 2-[(3-ethyl-3-oxetanyl)methyloxy]ethyl (meth)acrylate, 3-[(3-methyl-3-oxetanyl)methyloxy]propyl (meth)acrylate, 3-[(3-ethyl-3-oxetanyl)methyloxy]propyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate.

[0109] The second repeating unit is derived from a monomer having a functional group that reacts with a cyclic ether group. Examples of the functional group that reacts with a cyclic ether group include a hydroxyl group, a phenolic hydroxyl group, an organic acid, an acid anhydride, and an amino group. These functional groups are easily reactive with a cyclic ether group, and the functional group forms a crosslinked structure with the cyclic ether group, thereby improving the heat resistance and resistance to a stripping solution of the infrared cut filter. In particular, it is preferable that the functional group is an acidic functional group from the viewpoint of being easily reactive with a cyclic ether group. That is, it is preferable that the monomer containing a functional group that reacts with a cyclic ether group is acidic.

[0110] The functional group capable of reacting with the cyclic ether group is preferably a phenolic hydroxyl group among functional groups exhibiting acidity. The phenolic hydroxyl group exhibits weak acidity, so that the crosslinking reaction with the cyclic ether group is unlikely to occur during the polymerization process of the resin, but is likely to occur during the heating step in the preparation of the coating film. Therefore, the phenolic hydroxyl group is advantageous in terms of coatability.

[0111] The monomer having a phenolic hydroxyl group may be, for example, 4-hydroxyphenyl (meth)acrylate, N-(4-hydroxyphenyl) (meth)acrylamide, 3-(tert-butyl)-4-hydroxyphenyl (meth)acrylate, 4-(tert-butyl)-2-hydroxyphenyl (meth)acrylate, N-(4-hydroxyphenyl)maleimide, N-(3-hydroxyphenyl)maleimide, p-hydroxystyrene, and α-methyl-p-hydroxystyrene. The polymer produced using the monomer having a phenolic hydroxyl group contains a phenolic hydroxyl group in the side chain.

[0112] The copolymer may further include a third repeating unit. The third repeating unit is preferably derived from an acrylic monomer having an aromatic ring or an acrylic monomer having an alicyclic structure. The third repeating unit derived from an acrylic monomer having an aromatic ring is represented by the following formula (2). The third repeating unit derived from an acrylic monomer having an alicyclic structure is represented by the following formula (3).

[0113] [ka]

[0114] In the above formula (2), R4 is a hydrogen atom or a methyl group, and R5 is a single bond, a linear alkylene group having 1 or more carbon atoms, or a branched alkylene group having 3 or more carbon atoms. R6 is a hydrogen atom or a specific substituent. In formula (2), when R6 is a substituent, m is an integer of 1 to 5.

[0115] [ka]

[0116] In the above formula (3), R7 is a hydrogen atom or a methyl group, and R8 is a single bond, a linear alkylene group having 1 or more carbon atoms, or a branched alkylene group having 3 or more carbon atoms. In the formula (3), R9 is an alicyclic structure having 3 or more carbon atoms.

[0117] Examples of acrylic monomers having an aromatic ring include benzyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy polyethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, phenoxy polypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxypropyl hydrogen phthalate, ethoxylated ortho-phenylphenoxy. (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, 4-hydroxyphenyl (meth)acrylate, 2-naphthol (meth)acrylate, 4-biphenyl (meth)acrylate, 9-anthrylmethyl (meth)acrylate, 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl (meth)acrylate, phenol ethylene oxide (EO) modified acrylate, nonylphenol EO modified acrylate, 2-(meth)acryloyloxyethyl phthalate, and 2-(meth)acryloyloxyethyl hexahydrophthalate.

[0118] The acrylic monomer having an alicyclic structure may be, for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 4-t-cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, adamantyl (meth)acrylate, norbornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, and tetracyclododecyl (meth)acrylate.

[0119] The copolymer forming the infrared cut filter 13 contains a first repeating unit and a second repeating unit. Therefore, the cyclic ether group of the first repeating unit and the functional group reactive with the cyclic ether group of the second repeating unit form a crosslinked structure in the heating step during the filter formation, which prevents the transmittance of the infrared cut filter from changing due to heating and prevents the cyanine dye from eluting in the stripping solution used during dry etching. As a result, it is possible to improve the heat resistance and resistance to the stripping solution of the infrared cut filter.

[0120] The copolymer forming the infrared cut filter 13 further contains a third repeating unit. The aromatic ring or alicyclic structure of the third repeating unit is located between the cyanine dye and another cyanine dye located in the vicinity of the cyanine dye, thereby forming a distance between the cyanine dyes that is sufficient to suppress association of the cyanine dyes. This suppresses deterioration of the spectral characteristics at wavelengths that are expected to be absorbed by the cyanine dyes.

[0121] The copolymer preferably contains the first repeating unit in a proportion of 7.5% by weight to 17.5% by weight, and the ratio of the weight of the second repeating unit to the weight of the first repeating unit is preferably 1.0 to 3.0. By containing the first repeating unit and the second repeating unit in the above-mentioned ranges, a decrease in the infrared light absorbance of the infrared cut filter after heat treatment and stripping solution treatment is suppressed.

[0122] The copolymer preferably contains the third repeating unit in a proportion of 65% by weight or more. When the copolymer contains the third repeating unit in the above-mentioned range, association of the cyanine dye in the infrared cut filter is suppressed, and deterioration of the spectral characteristics at wavelengths expected to be absorbed by the cyanine dye is suppressed.

[0123] The copolymer preferably contains a first repeating unit derived from glycidyl methacrylate, a second repeating unit derived from 4-hydroxyphenyl methacrylate, and a third repeating unit derived from phenyl methacrylate. In this case, the copolymer preferably contains the third repeating unit in a ratio of 65% by weight to 70% by weight, and the ratio of the weight of the second repeating unit to the weight of the first repeating unit is preferably 1.0 to 3.0. As a result, the phenyl group of the third repeating unit is located between the other cyanine dyes located in the vicinity of the cyanine dye, so that a distance that suppresses the association of the cyanine dyes can be formed between the cyanine dyes. Therefore, the change in the spectral characteristics at the wavelength expected to be absorbed by the cyanine dye is suppressed. In addition, the phenol group of the second repeating unit is crosslinked with the epoxy group of the first repeating unit to form a crosslinked structure. This suppresses the change in transmittance of the infrared light cut filter 13 due to heating, and suppresses the elution of the infrared light absorbing dye into the stripping solution used during dry etching. As a result, it is possible to improve the heat resistance and resistance to the stripping solution in the infrared cut filter 13.

[0124] The copolymer preferably contains the first repeating unit in a ratio of 7.5% by weight to 17.5% by weight, which prevents a decrease in the infrared light absorbance of the infrared cut filter 13 after the heat treatment and the stripping solution treatment.

[0125] Furthermore, the copolymer preferably contains the second repeating unit in a ratio of 15% by weight to 25% by weight, which prevents a decrease in the infrared light absorbance of the infrared cut filter 13 after the heat treatment and the stripping solution treatment.

[0126] The copolymer may contain a monomer other than the above-mentioned acrylic monomer. The monomer other than the above-mentioned acrylic monomer may be, for example, a styrene-based monomer, a (meth)acrylic monomer, a vinyl ester-based monomer, a vinyl ether-based monomer, a halogen-containing vinyl-based monomer, and a diene-based monomer. The styrene-based monomer may be, for example, styrene, α-methylstyrene, p-methylstyrene, m-methylstyrene, p-methoxystyrene, p-hydroxystyrene, p-acetoxystyrene, vinyltoluene, ethylstyrene, phenylstyrene, and benzylstyrene. The (meth)acrylic monomer may be, for example, methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, and 2-ethylhexyl methacrylate. The vinyl ester-based monomer may be, for example, vinyl acetate. The vinyl ether-based monomer may be, for example, vinyl methyl ether. The halogen-containing vinyl-based monomer may be, for example, vinyl chloride. The diene monomer may be, for example, butadiene, isobutylene, etc. The copolymer may contain only one type of monomer other than the above-mentioned acrylic monomer, or may contain two or more types.

[0127] The copolymer may also contain a monomer for adjusting the polarity of the copolymer. The monomer for adjusting the polarity adds an acid group or a hydroxyl group to the copolymer. Such a monomer may be, for example, acrylic acid, methacrylic acid, maleic anhydride, maleic acid half ester, 2-hydroxyethyl acrylate, and 4-hydroxyphenyl (meth)acrylate.

[0128] The copolymer may have any of the following structures: random copolymer, alternating copolymer, block copolymer, and graft copolymer. If the copolymer has a random structure, the manufacturing process and preparation with the cyanine dye are easy. Therefore, the random copolymer is more preferable than other copolymers.

[0129] The polymerization method for obtaining the copolymer may be, for example, radical polymerization, cationic polymerization, anionic polymerization, living radical polymerization, living cationic polymerization, and living anionic polymerization. The polymerization method for obtaining the copolymer is preferably radical polymerization, since it is easy to produce industrially. The radical polymerization may be solution polymerization, emulsion polymerization, bulk polymerization, and suspension polymerization. The radical polymerization is preferably a solution polymerization. By using the solution polymerization, it is easy to control the molecular weight of the copolymer. Furthermore, the solution containing the copolymer after polymerization of the monomer can be used in the form of a solution for the manufacture of a filter for a solid-state imaging device.

[0130] In the radical polymerization, the above-mentioned monomer may be diluted with a polymerization solvent, and then a radical polymerization initiator may be added to polymerize the monomer. The polymerization solvent may be, for example, an ester-based solvent, an alcohol ether-based solvent, a ketone-based solvent, an aromatic solvent, an amide-based solvent, and an alcohol-based solvent. The ester-based solvent may be, for example, methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl lactate, ethyl lactate, and propylene glycol monomethyl ether acetate. The alcohol ether-based solvent may be, for example, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, 3-methoxy-1-butanol, and 3-methoxy-3-methyl-1-butanol. The ketone-based solvent may be, for example, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. The aromatic solvent may be, for example, benzene, toluene, and xylene. The amide-based solvent may be, for example, formamide and dimethylformamide. The alcohol-based solvent may be, for example, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, s-butanol, t-butanol, diacetone alcohol, and 2-methyl-2-butanol. Among these, ketone-based solvents and ester-based solvents are preferred because they can be used to manufacture filters for solid-state imaging devices. In addition, among the above-mentioned polymerization solvents, one type may be used alone, or two or more types may be used in combination.

[0131] In the radical polymerization, the amount of the polymerization solvent used is not particularly limited, but when the total amount of the monomers is set to 100 parts by weight, the amount of the polymerization solvent used is preferably 1 part by weight or more and 1,000 parts by weight or less, and more preferably 10 parts by weight or more and 500 parts by weight or less.

[0132] The radical polymerization initiator may be, for example, a peroxide or an azo compound. The peroxide may be, for example, benzoyl peroxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, and di-t-butyl peroxide. The azo compound may be, for example, azobisisobutyronitrile, azobisamidinopropane salt, azobiscyanovaleric acid (salt), and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].

[0133] The amount of radical polymerization initiator used is preferably 0.0001 parts by weight or more and 20 parts by weight or less, more preferably 0.001 parts by weight or more and 15 parts by weight or less, and even more preferably 0.005 parts by weight or more and 10 parts by weight or less, when the total amount of monomers is set to 100 parts by weight. The radical polymerization initiator may be added to the monomer and polymerization solvent before the start of polymerization, or may be dropped into the polymerization reaction system. Dropping the radical polymerization initiator into the polymerization reaction system for the monomer and polymerization solvent is preferable in that heat generation due to polymerization can be suppressed.

[0134] The reaction temperature of the radical polymerization is appropriately selected depending on the type of radical polymerization initiator and polymerization solvent. From the viewpoint of ease of production and reaction controllability, the reaction temperature is preferably 60° C. or more and 110° C. or less.

[0135] The glass transition temperature of the copolymer is preferably 75° C. or higher, and more preferably 100° C. or higher. If the glass transition temperature is 75° C. or higher, it is possible to increase the reliability of suppressing changes in the infrared light transmittance in the infrared cut filter when the infrared cut filter 13 is heated.

[0136] The molecular weight of the copolymer is preferably from 30,000 to 150,000, and more preferably from 50,000 to 150,000. When the molecular weight of the copolymer is within this range, it is possible to increase the certainty of suppressing changes in the infrared light transmittance when the infrared light cut filter 13 is heated.

[0137] A copolymer having a molecular weight of more than 150,000 is difficult to form into a coating liquid together with a cyanine dye due to an increase in viscosity during polymerization. Therefore, when the molecular weight of the copolymer exceeds 150,000, it is not easy to form the infrared cut filter 13. On the other hand, when the molecular weight of the copolymer is 150,000 or less, it is possible to form a coating liquid containing the copolymer and the cyanine dye, so that it is easier to form the infrared cut filter 13. The average molecular weight of the copolymer is a weight average molecular weight. The weight average molecular weight of the copolymer can be measured, for example, by gel permeation chromatography. For example, in a radical polymerization reaction, the molecular weight of the copolymer can be controlled by changing the concentration of the monomer and the radical polymerization initiator in the solution.

[0138] The percentage (MM / MS×100) of the mass of the monomer (MM) to the sum (MS) of the mass of the copolymer and the mass of the monomers constituting the copolymer is preferably 20% or less. Compared to a case where the amount of residual monomer is more than 20%, the infrared light transmittance of the cyanine dye is less likely to change when the infrared cut filter 13 is heated.

[0139] The percentage (MM / MS×100) of the mass of the monomer (MM) to the sum (MS) of the mass of the copolymer and the mass of the monomers constituting the copolymer is more preferably 10% or less, and even more preferably 3% or less. The mass of the copolymer and the mass of the monomer can be quantified based on the analysis results of the copolymer. The analysis method of the copolymer may be, for example, gas chromatography mass spectrometry (GC-MS), nuclear magnetic resonance spectroscopy (NMR), infrared spectroscopy (IR), etc.

[0140] The method for changing the ratio of the mass of the monomer to the sum of the mass of the copolymer and the mass of the monomer may be, for example, a method for changing the polymerization time, a method for changing the polymerization temperature, etc. Also, the method for changing the ratio of the mass of the monomer to the sum of the mass of the copolymer and the mass of the monomer may be a method for changing the concentration of the monomer and the radical polymerization initiator at the start of the polymerization reaction, etc. The method for changing the ratio of the mass of the monomer to the sum of the mass of the copolymer and the mass of the monomer may be a method for changing the purification conditions after the polymerization reaction, etc. Among these, the method for changing the polymerization time is preferred because it has high control accuracy for changing the ratio of the mass of the monomer.

[0141] When the radical polymerization initiator used in the polymerization of the copolymer is an organic peroxide having an aromatic ring in the side chain, the infrared cut filter preferably contains less than 0.35 parts by weight of the organic peroxide when the copolymer contained in the infrared cut filter is set to 100 parts by weight. By containing less than 0.35 parts by weight of the organic peroxide in the infrared cut filter, deterioration of the spectral characteristics of the infrared cut filter in the visible light region and the infrared light region is suppressed.

[0142] [Method of manufacturing filters for solid-state imaging devices] The method for manufacturing the filter 10F for solid-state imaging devices includes forming the infrared cut filter 13 and patterning the infrared cut filter 13 by dry etching. The infrared cut filter 13 is formed to contain a cyanine dye and a copolymer. The method for manufacturing the filter 10F for solid-state imaging devices will be described in more detail below.

[0143] Each of the color filters 12R, 12G, 12B, and 12P is formed by forming a coating film containing a colored photosensitive resin and patterning the coating film using a photolithography method. For example, the coating film containing a red photosensitive resin is formed by applying a coating liquid containing a red photosensitive resin and drying the coating film. The red filter 12R is formed by exposing the coating film containing a red photosensitive resin to an area corresponding to the red filter 12R and developing it. The green filter 12G, the blue filter 12B, and the infrared light pass filter 12P are also formed by the same method as the red filter 12R.

[0144] The pigments contained in the coloring compositions of the red filter 12R, the green filter 12G, and the blue filter 12B may be organic or inorganic pigments, either alone or in combination. The pigment is preferably a pigment having high color development and high heat resistance, particularly a pigment having high thermal decomposition resistance, and is preferably an organic pigment. The organic pigment may be, for example, a phthalocyanine-based, azo-based, anthraquinone-based, quinacridone-based, dioxazine-based, anthanthrone-based, indanthrone-based, perylene-based, thioindigo-based, isoindoline-based, quinophthalone-based, or diketopyrrolopyrrole-based pigment.

[0145] The coloring component contained in the infrared light pass filter 12P may be a black coloring matter or a black dye. The black coloring matter may be a single black coloring matter or a mixture of two or more black coloring matter. The black dye may be, for example, an azo dye, an anthraquinone dye, an azine dye, a quinoline dye, a perinone dye, a perylene dye, or a methine dye.

[0146] The photosensitive coloring composition of each color further contains a binder resin, a photopolymerization initiator, a polymerizable monomer, an organic solvent, a leveling agent, and the like. When forming the infrared cut filter 13, a coating liquid containing the above-mentioned cyanine dye, copolymer, and organic solvent is applied onto each of the color filters 12R, 12G, 12B, and 12P, and the coating film is dried. Next, the dried coating film is hardened by heating. In this way, the infrared cut filter 13 is formed.

[0147] When forming the through hole 13H of the infrared cut filter 13, first, a photoresist layer is formed on the infrared cut filter 13. The photoresist layer is patterned to form a resist pattern. Next, the infrared cut filter 13 is etched by dry etching using the resist pattern as an etching mask. Then, the resist pattern remaining on the infrared cut filter 13 after etching is removed with a stripping solution to form the through hole 13H. This allows the infrared cut filter to be patterned.

[0148] The stripping liquid may be a liquid capable of dissolving the resist pattern. The stripping liquid may be, for example, N-methylpyrrolidone or dimethylsulfoxide. The method for contacting the infrared cut filter 13 with the stripping liquid may be any method such as a dipping method, a spraying method, or a spinning method.

[0149] The barrier layer 14 is formed by a vapor phase film formation method such as a sputtering method, a CVD method, or an ion plating method, or a liquid phase film formation method such as a coating method. The barrier layer 14 made of silicon oxide is formed, for example, on a substrate on which an infrared light cut filter 13 is formed, through film formation by sputtering using a target made of silicon oxide. The barrier layer 14 made of silicon oxide is formed, for example, on a substrate on which an infrared light cut filter 13 is formed, through film formation by CVD using silane and oxygen. The barrier layer 14 made of silicon oxide is formed, for example, by applying a coating liquid containing polysilazane, modifying it, and drying the coating. The layer structure of the barrier layer 14 may be a single layer structure made of a single compound, a laminated structure of layers made of a single compound, or a laminated structure of layers made of different compounds.

[0150] Each of the microlenses 15R, 15G, 15B, and 15P is formed by forming a coating film containing a transparent resin, patterning the coating film using a photolithography method, and reflowing the coating film by a heat treatment. The transparent resin may be, for example, an acrylic resin, a polyamide resin, a polyimide resin, a polyurethane resin, a polyester resin, a polyether resin, a polyolefin resin, a polycarbonate resin, a polystyrene resin, or a norbornene resin.

[0151] [Production Example] [Production Example 1] Production Examples 1-1 to 1-6 will be described with reference to Table 1. In the copolymer produced by Production Example 1 described below, the weight ratio of each repeating unit in the produced copolymer is equal to the weight ratio of each monomer at the time of producing the copolymer.

[0152] [Table 1]

[0153] [Production Example 1-1] 300 parts by weight of propylene glycol monomethyl ether acetate (PGMAc) was prepared as a polymerization solvent, and 15 parts by weight of glycidyl methacrylate, 15 parts by weight of 4-hydroxyphenyl methacrylate, and 70 parts by weight of phenyl methacrylate were prepared as acrylic monomers.

[0154] Furthermore, 1.5 parts by weight of benzoyl peroxide (BPO) was prepared as a radical polymerization initiator. These were placed in a reaction vessel equipped with a stirrer and a reflux tube, and stirred and refluxed for 8 hours while heating to 80°C and introducing nitrogen gas into the reaction vessel. This resulted in a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate.

[0155] [Production Example 1-2] In Production Example 1-1, 4-hydroxyphenyl methacrylate was changed to N-(4-hydroxyphenyl) methacrylamide. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, N-(4-hydroxyphenyl) methacrylamide, and phenyl methacrylate was obtained in the same manner as in Production Example 1-1.

[0156] [Production Example 1-3] In Production Example 1-1, 4-hydroxyphenyl methacrylate was changed to N-(4-hydroxyphenyl)maleimide. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, N-(4-hydroxyphenyl)maleimide, and phenyl methacrylate was obtained in the same manner as in Production Example 1-1.

[0157] [Production Example 1-4] In Production Example 1-1, glycidyl methacrylate was changed to (3-ethyloxetan-3-yl)methyl methacrylate. Otherwise, a polymer solution containing a copolymer formed from (3-ethyloxetan-3-yl)methyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 1-1.

[0158] [Production Example 1-5] In Production Example 1-1, phenyl methacrylate was changed to dicyclopentanyl methacrylate. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and dicyclopentanyl methacrylate was obtained in the same manner as in Production Example 1-1.

[0159] [Production Example 1-6] In Production Example 1-1, 100 parts by weight of phenyl methacrylate was prepared as a monomer. A polymer solution containing a copolymer produced only from phenyl methacrylate was obtained in the same manner as in Production Example 1-1.

[0160] [Production Example 2] Production Examples 2-1 to 2-11 will be described with reference to Table 2. In Production Example 2, the first repeating unit is derived from glycidyl methacrylate (GMA), the second repeating unit is derived from 4-hydroxyphenyl methacrylate (HPMA), and the third repeating unit is derived from phenyl methacrylate (PhMA). In the copolymer produced by Production Example 2, the weight ratio of each repeating unit in the produced copolymer is equal to the weight ratio of each monomer at the time of producing the copolymer.

[0161] [Table 2]

[0162] [Production Example 2-1] In Production Example 1-1, the amount of glycidyl methacrylate was changed to 20 parts by weight, the amount of 4-hydroxyphenyl methacrylate was changed to 10 parts by weight, and the amount of phenyl methacrylate was changed to 70 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 0.5. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 1-1.

[0163] [Production Example 2-2] In Production Example 2-1, the amount of glycidyl methacrylate was changed to 15 parts by weight, and the amount of 4-hydroxyphenyl was changed to 15 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 1.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-1.

[0164] [Production Example 2-3] In Production Example 2-1, the amount of glycidyl methacrylate was changed to 10 parts by weight, and the amount of 4-hydroxyphenyl methacrylate was changed to 20 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 2.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-1.

[0165] [Production Example 2-4] In Production Example 2-1, the amount of glycidyl methacrylate was changed to 7.5 parts by weight, and the amount of 4-hydroxyphenyl methacrylate was changed to 22.5 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to glycidyl methacrylate was set to 3.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-1.

[0166] [Production Example 2-5] In Production Example 2-1, the amount of glycidyl methacrylate was changed to 6 parts by weight, and the amount of 4-hydroxyphenyl methacrylate was changed to 24 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 4.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-1.

[0167] [Production Example 2-6] In Production Example 2-1, the amount of glycidyl methacrylate was changed to 5 parts by weight, and the amount of 4-hydroxyphenyl methacrylate was changed to 25 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 5.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-1.

[0168] [Production Example 2-7] In Production Example 2-1, the amount of glycidyl methacrylate was changed to 17.5 parts by weight, the amount of 4-hydroxyphenyl methacrylate was changed to 17.5 parts by weight, and the amount of phenyl methacrylate was changed to 65 parts by weight. As a result, the ratio of the weight of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 1.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-1.

[0169] [Production Example 2-8] In Production Example 2-7, the amount of glycidyl methacrylate was changed to 11.5 parts by weight, and the amount of 4-hydroxyphenyl methacrylate was changed to 23.5 parts by weight. Thus, the weight ratio of 4-hydroxyphenyl methacrylate to glycidyl methacrylate was set to 2.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-7.

[0170] [Production Example 2-9] In Production Example 2-7, the amount of glycidyl methacrylate was changed to 10 parts by weight, and the amount of 4-hydroxyphenyl methacrylate was changed to 25 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to glycidyl methacrylate was set to 2.5. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-7.

[0171] [Production Example 2-10] In Production Example 2-7, the amount of glycidyl methacrylate was changed to 20 parts by weight, the amount of 4-hydroxyphenyl methacrylate was changed to 20 parts by weight, and the amount of phenyl methacrylate was changed to 60 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 1.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-7.

[0172] [Production Example 2-11] In Production Example 2-7, the amount of glycidyl methacrylate was changed to 25 parts by weight, the amount of 4-hydroxyphenyl methacrylate was changed to 25 parts by weight, and the amount of phenyl methacrylate was changed to 50 parts by weight. As a result, the weight ratio of 4-hydroxyphenyl methacrylate to the weight of glycidyl methacrylate was set to 1.0. Otherwise, a polymer solution containing a copolymer formed from glycidyl methacrylate, 4-hydroxyphenyl methacrylate, and phenyl methacrylate was obtained in the same manner as in Production Example 2-7.

[0173] [Test example] [Test Example 1] In Test Example 1, six types of infrared cut filters were obtained by using the copolymers of Production Examples 1-1 to 1-6 in the following manner. Then, for each infrared cut filter, the absorbance before the test, after the peeling solution resistance test, and after the heat resistance test was calculated in the manner described below. When producing the infrared cut filters of each test example, the infrared cut filter used in the peeling solution resistance test described below and the infrared cut filter used in the heat resistance test were produced separately.

[0174] A coating solution containing 0.3 g of cyanine dye, 12.0 g of 25% polymer solution, and 10 g of propylene glycol monomethyl ether acetate was prepared. In this case, a dye represented by the above formula (6) was used as the cyanine dye, and six types of polymer solutions containing the copolymers obtained by the above-mentioned Production Examples 1-1 to 1-6 were used. The coating solution was applied onto a transparent substrate, and the coating film was dried. Next, the coating film was heated at 230°C to harden it, thereby obtaining infrared light cut filters of Test Examples 1-1 to 1-6 having a thickness of 1.0 μm.

[0175] [Evaluation method] [Spectral characteristics] The transmittance of the infrared cut filter of each test example for light having each wavelength from 350 nm to 1150 nm was measured using a spectrophotometer (U-4100, manufactured by Hitachi High-Technologies Corporation). Then, the absorbance was calculated from the transmittance measurement results. In this way, an absorbance spectrum was obtained for each infrared cut filter. The absorbance spectrum of the cyanine dye represented by the above formula (6) has a peak at 950 nm. Therefore, it was evaluated whether the absorbance at 950 nm of each infrared cut filter was 0.8 or more. An infrared cut filter having an absorbance at 950 nm of 0.8 or more has an infrared light absorption ability suitable for application to a solid-state imaging device.

[0176] [Resistance to peeling liquid] After measuring the transmittance of the infrared cut filter of each test example, the infrared cut filter of each test example was immersed in the stripping solution for 1 minute. The transmittance of the infrared cut filter of each test example after immersion was measured by the same method as that for the infrared cut filter of each test example before immersion. Then, the absorbance was calculated from the transmittance measurement result. As a result, the absorbance spectrum was obtained for the infrared cut filter of each test example after immersion. Then, it was evaluated whether the absorbance at 950 nm of the infrared cut filter of each test example after immersion was 0.7 or more. Note that, in the infrared cut filter after immersion in the stripping solution, the infrared cut filter having an absorbance at 950 nm of 0.7 or more has an infrared light absorption ability suitable for application to a solid-state imaging device.

[0177] [Heat resistance] After measuring the transmittance of the infrared cut filter of each test example, the infrared cut filter of each test example was heated at 250°C. The transmittance of the infrared cut filter of each test example after heating was measured by the same method as that for the infrared cut filter of each test example before heating. Then, the absorbance was calculated from the transmittance measurement result. As a result, the absorbance spectrum was obtained for the infrared cut filter of each test example after heating. Then, it was evaluated whether the absorbance at 950 nm was 0.7 or more in the infrared cut filter of each test example after heating. Note that, in the infrared cut filter after heating at 250°C, the infrared cut filter having an absorbance at 950 nm of 0.7 or more has an infrared light absorption ability suitable for application to a solid-state imaging device.

[0178] [Evaluation Results] The absorbance of the infrared cut filters of Test Examples 1-1 to 1-6 was calculated, and the absorbance was as shown in the following Table 3. In each Test Example, it was found that the absorbance before the test of the infrared cut filter prepared for the peeling solution resistance test was the same as the absorbance before the test of the infrared cut filter prepared for the heat resistance test.

[0179] [Table 3]

[0180] As shown in Table 3, it was found that the absorbance before the resistance test in Test Examples 1-1 to 1-6 was 0.96.

[0181] As described above, it was confirmed that the absorbance at 950 nm of each infrared cut filter before the durability test was 0.8 or more for the infrared cut filters of Test Examples 1-1 to 1-6.

[0182] In addition, after the peeling solution resistance test, the absorbance of the infrared cut filter of Test Example 1-1, the infrared cut filter of Test Example 1-2, and the infrared cut filter of Test Example 1-3 was confirmed to be 0.85. The absorbance of the infrared cut filter of Test Example 1-4 was confirmed to be 0.77, the absorbance of the infrared cut filter of Test Example 1-5 was confirmed to be 0.74, and the absorbance of the infrared cut filter of Test Example 1-6 was confirmed to be 0.05.

[0183] In this way, it was found that in the copolymer, the first repeating unit has a cyclic ether group and the second repeating unit has a phenolic hydroxyl group, which is a functional group that reacts with the cyclic ether group, thereby improving the resistance of the infrared light cut filter to stripping solutions.

[0184] As shown in Table 3, after the heat resistance test, the absorbance of the infrared cut filter of Test Example 1-1 was 0.80, and the absorbance of the infrared cut filter of Test Example 1-2 and the infrared cut filter of Test Example 1-3 was 0.82. The absorbance of the infrared cut filter of Test Example 1-4 was 0.77, the absorbance of the infrared cut filter of Test Example 1-5 was 0.72, and the absorbance of the infrared cut filter of Test Example 1-6 was 0.30.

[0185] In this way, it was found that the heat resistance of the infrared light cut filter can be improved by having in the copolymer the first repeating unit have a cyclic ether group and the second repeating unit have a phenolic hydroxyl group, which is a functional group that reacts with the cyclic ether group.

[0186] From the above results, it was found that in the copolymer, the first repeating unit has a cyclic ether group and the second repeating unit has a functional group that reacts with the cyclic ether group, thereby achieving both resistance to stripping solutions and heat resistance of the infrared light cut filter.

[0187] [Test Example 2] In Test Example 2, 11 types of infrared cut filters were obtained by using the copolymers of Production Examples 2-1 to 2-11 in the same manner as in Test Example 1. Then, for each infrared cut filter, the absorbance before the test, after the peeling solution resistance test, and after the heat resistance test was calculated by the above-mentioned method. When producing the infrared cut filters of each test example, the infrared cut filter used in the peeling solution resistance test described below and the infrared cut filter used in the heat resistance test were produced separately.

[0188] [Evaluation method] The absorbance spectra were obtained for the infrared cut filters of Test Examples 2-1 to 2-11 using the same method as Test Example 1. In addition, the infrared cut filters of Test Examples 2-1 to 2-11 were subjected to a peeling solution resistance test and a heat resistance test using the same method as Test Example 1. Then, the absorbance spectra were obtained for the infrared cut filters after each test using the same method as Test Example 1.

[0189] [Evaluation Results] The absorbance of the infrared cut filters of Test Examples 2-1 to 2-11 was calculated, and the absorbance was as shown in the following Table 4. In each Test Example, it was found that the absorbance before the test of the infrared cut filter prepared for the peeling solution resistance test was the same as the absorbance before the test of the infrared cut filter prepared for the heat resistance test.

[0190] [Table 4]

[0191] As shown in Table 4, the absorbance before the resistance test in Test Example 2-1 to Test Example 2-9 was found to be 0.96. In contrast, the absorbance before the resistance test in Test Example 2-10 was found to be 0.68, and the absorbance before the resistance test in Test Example 2-11 was found to be 0.59.

[0192] Thus, it was found that the absorbance at 950 nm of the infrared cut filter before the test was 0.8 or more in Test Examples 2-1 to 2-9. In contrast, it was found that the absorbance at 950 nm of the infrared cut filter before the test was less than 0.8 in Test Examples 2-10 and 2-11.

[0193] That is, it was found that when the proportion of the third repeating unit in the copolymer was 65% by weight or more, the infrared cut filter favorably maintained the spectral characteristics before the test.

[0194] In addition, after the peeling solution resistance test, it was confirmed that the absorbance of the infrared cut filter of Test Example 2-1 was 0.02, and the absorbance of the infrared cut filter of Test Example 2-2 was 0.85. It was also confirmed that the absorbance of the infrared cut filter of Test Example 2-3 was 0.82, and the absorbance of the infrared cut filter of Test Example 2-4 was 0.72. It was also confirmed that the absorbance of the infrared cut filter of Test Example 2-5 was 0.30, and the absorbance of the infrared cut filter of Test Example 2-6 was 0.05.

[0195] It was confirmed that the absorbance of the infrared cut filter of Test Example 2-7 was 0.85, the absorbance of the infrared cut filter of Test Example 2-8 was 0.80, and the absorbance of the infrared cut filter of Test Example 2-9 was 0.72. It was also confirmed that the absorbance of the infrared cut filter of Test Example 2-10 was 0.64, and the absorbance of the infrared cut filter of Test Example 2-11 was 0.55.

[0196] Thus, it was found that the absorbance at 950 nm of the infrared cut filter after the stripping solution test was 0.7 or more in Test Examples 2-2 to 2-4 and Test Examples 2-7 to 2-9. In contrast, it was found that the absorbance at 950 nm of the infrared cut filter after the stripping solution test was less than 0.7 in Test Examples 2-1, 2-5, 2-6, 2-10, and 2-11.

[0197] In other words, it was found that the resistance of the infrared light cut filter to stripping solutions is improved when the proportion of the first repeating unit in the copolymer is 7.5% by weight or more and 17.5% by weight or less, and the ratio of the second repeating unit to the weight of the first repeating unit is 1.0 to 3.0.

[0198] In addition, as shown in Table 4, after the heat resistance test, the absorbance of the infrared cut filter of Test Example 2-1 and the infrared cut filter of Test Example 2-2 was 0.80, and the absorbance of the infrared cut filter of Test Example 2-3 was 0.82. In addition, the absorbance of the infrared cut filter of Test Example 2-4 and the infrared cut filter of Test Example 2-5 was 0.80, and the absorbance of the infrared cut filter of Test Example 2-6 was 0.82. And, the absorbance of the infrared cut filter of Test Example 2-7 was 0.72, and the absorbance of the infrared cut filter of Test Example 2-8 and the infrared cut filter of Test Example 2-9 was 0.80. Furthermore, the absorbance of the infrared cut filter of Test Example 2-10 was 0.40, and the absorbance of the infrared cut filter of Test Example 2-11 was 0.21.

[0199] Thus, it was confirmed that the absorbance at 950 nm of the infrared cut filter after the heat resistance test was 0.7 or more in Test Examples 2-1 to 2-9. In contrast, it was confirmed that the absorbance at 950 nm of the infrared cut filter after the heat resistance test was less than 0.7 in Test Examples 2-10 and 2-11. That is, it was confirmed that the heat resistance of the infrared cut filter was maintained when the ratio of the weight of the first repeating unit to the weight of the second repeating unit was in the range of 0.5 to 5.0, and that the heat resistance was improved by having the third repeating unit be 65 wt % or more.

[0200] As described above, according to one embodiment of the infrared cut filter, the filter for a solid-state imaging device, the solid-state imaging device, and the method for manufacturing the filter for a solid-state imaging device, the following effects can be obtained.

[0201] (1) A crosslinked structure is formed by crosslinking a cyclic ether group of the first repeating unit with a functional group that reacts with a cyclic ether group of the second repeating unit. This prevents the transmittance of the infrared cut filter 13 from changing due to heating, and prevents the infrared absorbing dye from eluting into the stripping solution used during dry etching. As a result, it is possible to improve the heat resistance and resistance to the stripping solution of the infrared cut filter 13.

[0202] (2) It is preferable that the monomer containing a cyclic ether group contains at least one of an epoxy group and an oxetanyl group from the viewpoint of reactivity between the cyclic ether group and a functional group reactive with the cyclic ether group contained in the second repeating unit.

[0203] (3) Since the functional group that reacts with the cyclic ether group is acidic, the crosslinking reaction can be prevented from immediately proceeding at room temperature during the resin polymerization process. (4) Because phenolic hydroxyl groups are weakly acidic, crosslinking reactions with cyclic ether groups are unlikely to occur during the polymerization process of the resin, but are likely to occur during the heating process when forming a coating film. Therefore, phenolic hydroxyl groups are advantageous in terms of coatability.

[0204] (5) The aromatic or alicyclic group of the third repeating unit is located between the cyanine dye and another cyanine dye located in the vicinity of the cyanine dye, so that a distance sufficient to suppress association of the cyanine dyes can be formed between the cyanine dyes, thereby suppressing changes in the spectral characteristics at the wavelengths expected to be absorbed by the cyanine dyes.

[0205] (6) When the copolymer contains the first repeating unit and the second repeating unit in the above-mentioned range, a decrease in the infrared light absorbance in the infrared cut filter 13 is suppressed after the heat treatment and the stripping solution treatment.

[0206] (7) When the copolymer contains the third repeating unit at a ratio of 65% by mass or more, the deterioration of the spectral characteristics of the infrared cut filter 13 at wavelengths expected to be absorbed by the cyanine dye is suppressed.

[0207] (8) If the glass transition temperature of the copolymer is 75° C. or higher, it is possible to increase the certainty of suppressing changes in the infrared light transmittance when the infrared cut filter 13 is heated.

[0208] (9) If the average molecular weight of the copolymer is 30,000 or more and 150,000 or less, it is possible to increase the certainty of suppressing changes in the infrared light transmittance when the infrared cut filter 13 is heated.

[0209] (10) When the residual monomer content is 20% or less, the infrared light transmittance of the cyanine dye is less likely to change when the infrared cut filter is heated, compared with when the residual monomer content is more than 20%.

[0210] (11) The barrier layer 14 prevents an oxidation source from reaching the infrared cut filter 13, so that the infrared cut filter 13 is less likely to be oxidized by the oxidation source.

[0211] [Example of change] The above-described embodiment can be modified as follows. [Barrier layer] The barrier layer 14 is not limited to being disposed between the infrared cut filter 13 and the microlenses 15R, 15G, 15B, and 15P, but may be disposed on the outer surface of each of the microlenses 15R, 15G, 15B, and 15P.

[0212] The solid-state imaging device 10 may include an anchor layer between the barrier layer 14 and the layer below the barrier layer 14. In this case, the adhesion between the barrier layer 14 and the layer below the barrier layer 14 is increased by the anchor layer. The solid-state imaging device 10 may also include an anchor layer between the barrier layer 14 and the layer above the barrier layer 14. In this case, the adhesion between the barrier layer and the layer above the barrier layer is increased by the anchor layer. The material forming the anchor layer is, for example, a polyfunctional acrylic resin or a silane coupling agent.

[0213] The layer structure of the barrier layer 14 may be a single layer structure made of a single compound, a laminate structure of layers made of a single compound, or a laminate structure of layers made of different compounds.

[0214] The barrier layer 14 may function as a planarizing layer that fills in the step formed between the surface of the infrared cut filter 13 and the surface of the infrared pass filter 12P. The solid-state imaging device filter 10F does not have to include the barrier layer 14. Even in this case, it is possible to obtain the effect equivalent to the above-mentioned (1).

[0215] [others] The thickness of each of the color filters 12R, 12G, 12B may be equal to or different from that of the infrared pass filter 12P. The thickness of each of the color filters 12R, 12G, 12B may be, for example, 0.5 μm or more and 5 μm or less.

[0216] The color filter may be a three-color filter consisting of a cyan filter, a yellow filter, and a magenta filter.The color filter may be a four-color filter consisting of a cyan filter, a yellow filter, a magenta filter, and a black filter.The color filter may be a four-color filter consisting of a transparent filter, a yellow filter, a red filter, and a black filter.

[0217] The color filters 12R, 12G, and 12B may have the same thickness as the infrared pass filter 12P, or may have different thicknesses. The thickness of each of the color filters 12R, 12G, and 12B may be, for example, 0.5 μm or more and 5 μm or less.

[0218] The material forming the infrared light cut filter 13 may contain additives that combine other functions, such as a light stabilizer, an antioxidant, a heat stabilizer, and an antistatic agent. The solid-state imaging element 10 has an oxygen permeability of 5.0 cc / m 2 For example, the laminated structure may be a functional layer such as a flattening layer or an adhesive layer, and may have an oxygen permeability of 5.0 cc / m 2 or less together with each microlens. 2 It may be less than / day / atm.

[0219] The solid-state imaging element 10 may include a bandpass filter on the light incident surface side of the multiple microlenses. The bandpass filter is a filter that transmits only light having a specific wavelength of visible light and near-infrared light, and has a similar function to the infrared light cut filter 13. In other words, the bandpass filter can cut out unnecessary infrared light that can be detected by the photoelectric conversion elements 11R, 11G, and 11B for each color. This can improve the detection accuracy of visible light by the photoelectric conversion elements 11R, 11G, and 11B for each color, and the detection accuracy of near-infrared light having a wavelength in the 850 nm or 940 nm band that is the detection target of the infrared photoelectric conversion element 11P. [Explanation of symbols]

[0220] 10...Solid-state image sensor 10F…Solid-state image sensor filter 11...Photoelectric conversion element 12R…Red filter 12G…Green filter 12B…Blue filter 12P…Infrared pass filter 13…Infrared cut filter 13H...Through hole 14...Barrier layer 15B…Blue microlens 15G…Green microlens 15P…Infrared microlens 15R…Red microlens

Claims

1. a cyanine dye comprising polymethine, a cation having two nitrogen-containing heterocycles, one at each end of the polymethine, and tris(pentafluoroethyl)trifluorophosphate; an infrared light cut filter comprising: a copolymer represented by the following formula (1) and comprising a first repeating unit derived from an acrylic monomer containing a cyclic ether group, and a second repeating unit derived from a monomer containing a functional group reactive with the cyclic ether group; A photoelectric conversion element is provided. Solid-state imaging element. [Formula 1] In formula (1), R1 is a hydrogen atom or a methyl group, R2 is a single bond, a linear alkylene group having one or more carbon atoms, or a branched alkylene group having three or more carbon atoms, and R3 is a cyclic ether group containing an oxygen atom and two or more carbon atoms.

2. The monomer containing a cyclic ether group contains at least one of an epoxy group and an oxetanyl group. The solid-state imaging device according to claim 1 .

3. The monomer containing a functional group capable of reacting with a cyclic ether group exhibits acidity.

3. The solid-state imaging device according to claim 1.

4. The functional group that reacts with the cyclic ether group is a phenolic hydroxyl group. The solid-state imaging device according to claim 1 .

5. The copolymer contains a third repeating unit derived from an acrylic monomer having an aromatic ring represented by the following formula (2): The solid-state imaging device according to claim 1 . [chemical 2] In formula (2), R4 is a hydrogen atom or a methyl group, R5 is a single bond, a linear alkylene group having 1 or more carbon atoms, or a branched alkylene group having 3 or more carbon atoms. R6 is a hydrogen atom or a specified substituent. In formula (2), when R6 is a substituent, m is an integer of 1 to 5.

6. The copolymer includes a third repeating unit derived from an acrylic monomer having an alicyclic structure represented by the following formula (3): The solid-state imaging device according to claim 1 . [C3] In formula (3), R7 is a hydrogen atom or a methyl group, R8 is a single bond, a linear alkylene group having 1 or more carbon atoms, or a branched alkylene group having 3 or more carbon atoms, and R9 is an alicyclic structure having 3 or more carbon atoms.

7. The copolymer contains 7.5% by weight or more and 17.5% by weight or less of the first repeating unit, and The ratio of the weight of the second repeating unit to the weight of the first repeating unit is 1.0 or more and 3.0 or less. The solid-state imaging device according to claim 1 .

8. The copolymer contains 65% by weight or more of the third repeating unit.

7. The solid-state imaging device according to claim 5.

9. The infrared cut filter is provided with a barrier layer that prevents the passage of an oxidation source that oxidizes the infrared cut filter. The solid-state imaging device according to claim 1 .

10. A visible light filter; An infrared pass filter is provided. The solid-state imaging device according to claim 1 .

11. The oxygen permeability of the laminate structure located on the side of the incident surface of the infrared light cut filter is 5.0 cc / m 2 / day / atm or less The solid-state imaging device according to claim 1 .

12. Equipped with a bandpass filter that transmits only light with specific wavelengths of visible and near-infrared light The solid-state imaging device according to claim 1 .

Citation Information

Patent Citations

  • Infrared absorptive liquid composition, infrared cut filter and production method thereof using it, and camera module and production method thereof

    JP2013155353A

  • Infrared light cut filter, filter for solid-state image sensor, solid-state image sensor, and method for manufacturing filter for solid-state image sensor

    JP7556224B2

  • Optical filter

    WO2008072537A1

  • Near-infrared absorbing composition, near-infrared blocking filter, method for producing near-infrared blocking filter, solid-state imaging element, camera module and image display device

    WO2017047230A1

  • Thermally curable resin composition

    WO2017098996A1